2014
DOI: 10.1017/s0007114514002001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an energy-restricted diet rich in plant-derived α-linolenic acid on systemic inflammation and endothelial function in overweight-to-obese patients with metabolic syndrome traits

Abstract: Plant-derived a-linolenic acid (ALA) may reduce the risk of CVD, possibly by decreasing systemic inflammation and improving endothelial function. In the present study, the effects of a hypoenergetic diet rich in ALA (3·4 g/d) on the biomarkers of systemic inflammation and vascular function were investigated in eighty-one overweight-to-obese patients with metabolic syndrome traits in comparison with a hypoenergetic diet low in ALA (0·9 g/d, control). After a 6-month dietary intervention, there were significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 53 publications
(56 reference statements)
3
42
0
Order By: Relevance
“…However, the same study has revealed a large heterogeneity in FMD response to weight loss, which appeared to be related not only to the degree of weight reduction, but also to the presence of co-morbidities, the type of diet taken, and the concomitant use of medication and exercise therapy. Similar improvement in endothelial cell function, but also similar variability, has been demonstrated by using biochemical parameters of endothelial cell status, such as adhesion molecules (sICAM-1, E-selectin, VCAM-1) or hemostasis regulators (PAI-1, t-PA, vWF) [4,7,10,12].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, the same study has revealed a large heterogeneity in FMD response to weight loss, which appeared to be related not only to the degree of weight reduction, but also to the presence of co-morbidities, the type of diet taken, and the concomitant use of medication and exercise therapy. Similar improvement in endothelial cell function, but also similar variability, has been demonstrated by using biochemical parameters of endothelial cell status, such as adhesion molecules (sICAM-1, E-selectin, VCAM-1) or hemostasis regulators (PAI-1, t-PA, vWF) [4,7,10,12].…”
Section: Introductionsupporting
confidence: 59%
“…The lack of an unequivocal answer in this respect results mainly from large variability across the populations in the parameters assessed [7,12,13]. It may signify the true absence of such an effect, but it may also indicate that the parameters chosen to reflect the endothelial cell status are not sensitive enough.…”
Section: Introductionmentioning
confidence: 99%
“…Hypercholesterolaemic patients who consumed 6-8 g/d ALA for 2 years had a 12.5% decrease in blood CRP concentration, although there was no change in sICAM-1, IL-6 or IL-10 concentrations [261]. Egert et al reported that consuming 0.9 g/d or 3.4 g/d ALA significantly decreased the serum concentrations of CRP, TNF-α, IL-6, sICAM-1 and sEselectin in male and female subjects [257]. High ALA intake led to more a pronounced reduction in the serum concentration of YKL-40 compared to the lower intake of ALA [257].…”
Section: Alpha-linolenic Acid Stearidonic Acid and Inflammationmentioning
confidence: 99%
“…Egert et al reported that consuming 0.9 g/d or 3.4 g/d ALA significantly decreased the serum concentrations of CRP, TNF-α, IL-6, sICAM-1 and sEselectin in male and female subjects [257]. High ALA intake led to more a pronounced reduction in the serum concentration of YKL-40 compared to the lower intake of ALA [257]. Two recent studies which investigated the effect of increased ALA intake in patients receiving haemodialysis reported significant decreases in CRP concentrations after 8 weeks consuming 40 g/d ground flaxseed [244] or after consuming 30 g/d milled sesame, pumpkin and flaxseed mixture for 12 weeks [146].…”
Section: Alpha-linolenic Acid Stearidonic Acid and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation